IMPLEMENTATION STRATEGIES OF CHATGPT IN ENHANCING STUDENTS’ COMMUNICATION SKILLS IN THE GLOBAL BUSINESS CONTEXT - Mustafa, Fahrina; Siminto; Ausat, Abu Muna Almaududi (Technopreneurship and Educational Development Review (TENDER), 2024)
Effective communication skills are crucial in an increasingly interconnected global business environment. The ability to communicate clearly and persuasively, both orally and in writing, is key to fostering successful business relationships and overcoming cross-cultural challenges. This research aims to explore the implementation strategies of ChatGPT in enhancing students' communication skills, particularly within the global business context. The study adopts a qualitative literature review approach. Data for this research were sourced from scholarly articles available on Google Scholar, published between 2015 and 2024. The study findings indicate that implementing ChatGPT in education as an innovative strategy to enhance students' communication skills in the global business context holds significant potential in preparing the next generation for challenges in an increasingly interconnected and multicultural workplace. With its ability to provide real-time natural language interactions, ChatGPT not only aids in training students' communication skills but also prepares them to navigate various international business scenarios.